2002
DOI: 10.1080/000155502320624050
|View full text |Cite
|
Sign up to set email alerts
|

IgE-mediated Hypersensitivity Against Human Sweat Antigen in Patients with Atopic Dermatitis

Abstract: Sweating aggravates itch in atopic dermatitis, but the mechanism is unclear. In this study, we examined the involvement of type I hypersensitivity in the aggravation of atopic dermatitis by sweating. Skin tests with autologous sweat were positive in 56 of 66 patients (84.4%) with atopic dermatitis, but only in 3 of 27 healthy volunteers (11.1%). Sweat samples from both patients and healthy volunteers induced varying degrees of histamine release from basophils of patients with atopic dermatitis. However, the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…The IgE-binding ability of a patient's serum was inhibited by sweat but not by mite or Staphylococcus antigens, suggesting that antigens on the skin surface are unlikely to be responsible. Similar to CU, positive intradermal skin tests have been noted in AD patients [34,35]. It has been shown that the sweatinduced release of histamine from basophils is mediated by specifi c IgE for the partially purifi ed antigen in the sweat of patients with AD.…”
Section: Sweat Hypersensitivity In Cholinergic Urticaria and Atopic Dmentioning
confidence: 96%
“…The IgE-binding ability of a patient's serum was inhibited by sweat but not by mite or Staphylococcus antigens, suggesting that antigens on the skin surface are unlikely to be responsible. Similar to CU, positive intradermal skin tests have been noted in AD patients [34,35]. It has been shown that the sweatinduced release of histamine from basophils is mediated by specifi c IgE for the partially purifi ed antigen in the sweat of patients with AD.…”
Section: Sweat Hypersensitivity In Cholinergic Urticaria and Atopic Dmentioning
confidence: 96%
“…The characteristic distribution of skin lesions of AD, such as face, neck, cubital, and popliteal fossae, implies the association between exacerbation of AD and sweating. Moreover, we and other authors reported that skin test with autologous sweat was positive in the majority of patients with AD 5,6 and that clinical symptoms of children with AD significantly improved during the summer if they took showers at schools. [7][8][9] We previously revealed that semipurified sweat antigen, which was obtained from human sweat by a combination of various chromatography steps, induced histamine release from the basophils of 77% of patients with AD 10 and 66% of patients with cholinergic urticaria.…”
mentioning
confidence: 98%
“…Sweat is also known as an aggravating factor for AD, and immune reactions have been shown against sweat antigen in AD patients [41,42]. As known in miliaria rubra, the obstruction of sweat ducts causes the leaking of sweat into the epidermis, which provokes a local inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%